The anthropology of precious minerals - Ferry, Elizabeth Emma.; Vallard, Annabel; Walsh, Andrew, 1969- (Toronto : University of Toronto Press, 2020)
Based on a Wenner-Gren international workshop, held at the Royal Ontario Museum, this book addresses the complexity of human-mineral engagements through ethnographic case studies and anthropological reflections on different people and the minerals they deem 'precious.'
Introduction: engaging precious minerals / Andrew Walsh, Elizabeth Ferry, and Annabel Vallard -- Introduction to part one: scrappers, miners, and hunters / Susan D. Gillespie -- "Check out that gold-plated board!" scrapping cellphones and electronics in North America / Joshua A. Bell -- What is "artisanal" about "artisanal mining"? reflections from Madagascar's sapphire trade / Andrew Walsh -- The value and social lives of alpine crystals / Gilles Raveneau -- Introduction to part two: making preciousness: distinction and refraction / Elizabeth Ferry -- When stones become gems: valuations of minerals in Thailand / Annabel Vallard -- Transparent minerals and opaque diamond sources / Filipe Calvão -- Gold, ontological difference, and object agency / Les W. Field -- Afterward: facets of preciousness / Andrew Walsh, Elizabeth Ferry, and Annabel Vallard.
Includes bibliographical references and index.
Keywords: Precious metals -- Social aspects; Mineral industries -- Social aspects; Mines and mineral resources -- Social aspects; Metal-work -- Social aspects; Anthropology